2009
DOI: 10.1017/s1041610209991438
|View full text |Cite
|
Sign up to set email alerts
|

Dental health of community-living older people attending secondary healthcare: a cross-sectional comparison between those with and without diagnosed mental illness

Abstract: Dental problems are common in community-living older people, especially those with some natural remaining teeth and those with mental illness. There is a need to develop integrated mental health and dental care services for older people with emphasis on prevention of dental problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Among dentate patients, we found cognitive impairment to be associated with a reduced number of teeth and an increased need for dental treatment. Other authors have found similar results (11). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Among dentate patients, we found cognitive impairment to be associated with a reduced number of teeth and an increased need for dental treatment. Other authors have found similar results (11). …”
Section: Discussionsupporting
confidence: 83%
“…Suboptimal oral health has been self-reported among patients with SMI (3). Several reports detailing the oral health status of psychiatric patients in Denmark (4), The Netherlands (5), Italy (6), Spain (7), India (8), South Wales (9), Israel (10), United Kingdom (11) and Turkey (12) have revealed that mental illness and the medications used to treat the disorder can cause and magnify the severity of dental diseases with particular emphasis on caries experience (13). …”
Section: Introductionmentioning
confidence: 99%
“…2). We used the same community controls for two studies and so divided the number by two for each comparison (40,47,61).…”
Section: Edentulismmentioning
confidence: 99%
“…Purandare and colleagues [15] compared the dental health of older people who had psychiatric illness with those without. In general, the 103 people who had a psychiatric illness were younger and physically healthier but cognitively, socially and functionally more impaired than the control group (99 people).…”
Section: Key Pointsmentioning
confidence: 99%